Exploring deepfake technology: creation, consequences and countermeasures - Alanazi, Sami; Asif, Seemal (Springer, 2024)
This paper presents a comprehensive examination of deepfakes, exploring their creation, production and identification. Deepfakes are videos, images or audio that are remarkably realistic and generated using artificial intelligence algorithms. While they were initially intended for entertainment and commercial use, their harmful social consequences have become more evident over time. These technologies are now being misapplied for the creation of explicit content, coercing individuals and disseminating false information, resulting in an erosion of and potentially negative societal consequences. The paper also highlights the significance of legal regulations in controlling the utilization of deepfakes and investigates methods for their identification through machine learning. In the modern digital world, comprehending the ethical and legal implications of deepfakes necessitates a thorough understanding of the phenomenon.
Keywords: 36 Creative Arts and Writing; 46 Information and Computing Sciences; 3605 Screen and Digital Media; Machine Learning and Artificial Intelligence; Networking and Information Technology R&D (NITRD); Deepfake; GAN; false information; detection methods; image alteration; counterfeit content; realistic videos